Contribution of the CBCT in the diagnosis and treatment plan of odontogenic maxillary sinusitis: Cases Reports - Premoli Maciel, Aloizio (2020)
Objective: Report two cases of Odontogenic Maxillary Sinusitis (OMS), diagnosed exclusively by Cone Bean Computed Tomography (CBCT). Case Report 1: A 48 years-old woman referred diﬀuse pain across the face and upper left ﬁrst molar (ULFM) with carious lesion. The panoramic X-Ray showed a periapical lesion with delimited limits in the ULFM and opaciﬁcation of the left maxillary sinus (OPMS). Only in CBCT there were relationship between ULFM periapical lesion and the maxillary sinus through cortical rupture of the maxillary sinus ﬂoor, thickening the maxillary sinus mucosa (TMSM). The OMS was diagnosed as a periapical cyst invol- ving the ULFM. She was referred to endodontic treatment. Case Report 2: A 33 years-old man referred diﬀuse pain though the face and in upper right ﬁrst molar (URFM). The panoramic X-Ray showed a bone rarefaction without limits and vertical bone loss around the roots of URFM. The CBCT showed the same features of Case 1. Due the great TMSM a diﬀerential diagnosis between periodontal disease and maxillary sinus tumor was done. The diagnose of OMS and periodontal disease was done. The maxillary sinus was surgery explored though the oral communication of the dental extraction and the remaining communication. Conclusion: The CBCT impro- ved the details of infectious focus, alveolar bone and maxillary sinus involvement as well a better anatomical visualization between the aﬀected teeth and the maxillary sinus which were not observed on 2D x-rays images.